FEATURES OF THE FORMATION OF SPEECH REGULATORY FUNCTION IN CHILDREN WITH ATTENTION DEFICIT HYPERACTIVITY SYNDROME - Kozynets , Oleksandr; Lytvynenko, Olena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The concept of «regulatory function of speech» is considered, in particular, its formation in children with attention deficit hyperactivity disorder. Three stages of organizing speech therapy classes with this category of children are proposed.